PELAKSANAAN ASESMEN PEMBELAJARAN MATEMATIKA SMP SELAMA MASA PANDEMI COVID-19 - Nabilah Fauziah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
The purpose of this study was to find out how the process of implementing junior high school mathematics learning assessments was carried out during the covid-19 pandemic. This research uses a qualitative approach with descriptive method. Data collection techniques used observation, interviews, and documentation, with the research time starting from November 8, 2021 to November 30, 2021. The research subjects were mathematics teachers at SMP Negeri 19 Kota Tangerang. Based on the analysis of the research result, it was found that the implementation of the mathematics learning assessment middle school during the covid-19 pandemic at SMP Negeri 19 Kota Tangerang has been going quite well, focusing more on the implementation of assessments in the cognitive and psychomotor domains. In the implementation of the assessment of junior high school mathematics learning during the covid-19 pandemic, there are various obstacles, ranging from learning objectives that can’t be realized perfectly, learning materials that can’t be conveyed all, and students honestly in working on problems. In addition, the teacher also have difficulty in making assessments because during the pandemic students were given multiple choice questions via Google Form and didn’t include how to answer them, thus making the teacher doubt about the level of understanding and ability of students and the activity of students who were felt to be lacking.